INDIGENIOUS KNOWLEDGE OF URUG SOCIETIES FOR AGRICULTURE IRRIGATION IN BOGOR WEST JAVA - Bahagia Bahagia; Fachruddin Majeri Mangunjaya; Zuzy Anna; Rimun Wibowo (Universitas Djuanda Bogor, 2020)
The objective of this research to investigate traditional agricultural irrigation based on indigenious knowledge of customary urug societies in Bogor West Java. The research method use is Ethnoecology qualitative approach. This method is implemented because research have conection among human (cultural & social) and environment including traditional agriculture water management as well as the knowledge about environment. Data are collected by in-depth interview, observation and documentation. In order to determine respondents as major sources information use purposive sampling technique. The outcome is analized with combination numerous of method such as in-dept interview, observation, and documentation (triangulation data). There are some results including rice paddy field in Urug societies exert traditional terrascering for inventing land for cultivating of paddy because geograhpycally location of wet land paddy is mountainious. The another is traditional irrigation of Urug slue river water (main sources of irrigation) to to susukan (traditional reservoir). After that water is flowed to Selokan and continue to rice paddy field. The person who have mandatory for water agriculture management is mentioned as Ulu-ulu. Ulu-ulu is pivotal person because have chores for ensuring all farmer received water from river, Susukan and selokan. The other finding is Urug customary societies applicate gotong royong (mutual cooperation) among member of societies typically in traditional agriculture irrigatin activity. Keywords: Indigenious Knowledge, Susukan, Ulu-ulu, Traditional irrigation, traditional agriculture